The wisdom of Egypt : Jewish, early Christian, and gnostic essays in honour of Gerard P. Luttikhuizen - Hilhorst, A.; Kooten, Geurt Hendrik van, 1969-; Luttikhuizen, Gerard P. (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 2005)
This collection of essays gives a vivid impression of Egypt as background and stage of Jewish, Christian, and Gnostic thought and life in antiquity. It demonstrates Egypt's important role in the history, literature and culture of these religions.